Empowerment of Family Communications in Engagement Effectiveness of Family Members in Pandemic Times - S. Bekti Istiyanto; Ifan Iskandar; Maulina Larasati Putri; Kiki Dwi Arviani; Hana Hanifah (Tecno Scientifica Publishing, 2022)
Families are essential to a healthy and prosperous society. During a pandemic, the family's role in the development of family elements is diminished. The research question is whether family communication exists regarding family members' engagement during a pandemic. The study's objective was to ascertain the effect of family communication on family members' involvement during a pandemic. The term